Design and performance characterization of a soft robot hand with fingertip haptic feedback for teleoperation. (1st December 2020) - Li, Min; Zhuo, Yueyan; Chen, Jiazhou; He, Bo; Xu, Guanghua; Xie, Jun; Zhao, Xingang; Yao, Wei
ABSTRACT: A soft robot hand with fingertip haptic feedback for teleoperation is proposed to perform complex tasks and ensure safe and friendly human-machine interaction. This robot hand can perform finger flexion/extension and abduction/adduction motions. A data glove is used to collect the hand joint angle data of the operator. Flexion sensors are embedded in the soft robot hand to monitor the bending angles of the actuators. Pressure sensors on the fingertips of the robot hand collect contact force data, and haptic feedback actuators located on the fingertips of the operator display the contact force to the operator. Characterization tests and teleoperation performance tests involving human participants are performed to prove the feasibility of the soft robot hand. The soft robot hand prototype satisfies the output force requirements and can meet 96.86% of the design requirements of the joint angles. The soft robot hand can be teleoperated to perform nine commonly used motions in daily operational tasks. The success rates of fingertip force discrimination, grasp, and pinch ability experiment are 100%, 95.00%, and 98.33%, respectively. The results of the experiment suggest that the soft robot hand with fingertip haptic feedback can perform complex tasks in teleoperation. GRAPHICAL ABSTRACT: UF0001